Reading the Fifth Veda Studies on the Mahabharata-- Essays by Alf Hiltebeitel. Volume 1. - Adluri, V. (Numen Book Series, 2011)
Often spoken of as the 'Fifth Veda', id est, as a text in continuity with the four Vedas and outweighing them all in size and import, the Mahābhārata presents a complex mythological and narrative landscape, incorporating fundamental ethical, social, philosophic, and pedagogic issues. In a series of position pieces and essays written over a span of 30 years, Alf Hiltebeitel, Columbian Professor of Religion, History, and Human Sciences at The George Washington University, articulates a compelling new approach to the epic: as a literary work of fundamental theological and philosophical significance rich in metaphor and meaning. In this three-part volume, the editors gather some of Hiltebeitel's seminal writings on the epic along with new pieces written especially for the volume. This two volume edition collects nearly three decades of Alf Hiltebeitel's researches into the Indian epic and religious tradition. The two volumes document Hiltebeitel's longstanding fascination with the Sanskrit epics: volume 1 presents a series of appreciative readings of the Mahābhārata (and to a lesser extent, the Rāmāyaṇa), while volume 2 focuses on what Hiltebeitel has called "the underground Mahābhārata," id est, the Mahābhārata as it is still alive in folk and vernacular traditions. Recently re-edited and with a new set of articles completing a trajectory Hiltebeitel established over 30 years ago, this work constitutes a definitive statement from this major scholar. Comprehensive indices, cross-referencing, and an exhaustive bibliography make it an essential reference work. For more information on the second volume please click here .